2013
DOI: 10.1371/journal.pone.0073591
|View full text |Cite
|
Sign up to set email alerts
|

Aldose Reductase Is Involved in the Development of Murine Diet-Induced Nonalcoholic Steatohepatitis

Abstract: Hepatic aldose reductase (AR) expression is known to be induced in liver diseases, including hepatitis and hepatocellular carcinoma. However, the role of AR in the development of these diseases remains unclear. We performed this current study to determine whether and how AR might be involved in the development of diet-induced nonalcoholic steatohepatitis. Our results showed that the level of AR protein expression was significantly higher in db/db mice fed the methionine-choline-deficient (MCD) diet than in mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…Moreover, MMP-2 has been shown to be upregulated in rat models of choline deficiency-mediated liver cirrhosis [54][55][56][57] and a similar pattern of expression has been observed for TIMP-1 (a) (b) Figure 1 Representative photos indicating the expression of the studied proteins (by brown staining) in the: (a) myocardium, interstitium and vessels; (b) interstitium and vessels (9200). [54,57,58], TIMP-2 [54] and MMP-9 [57]. On the contrary, the impact of inadequate levels of carnitine on MMPs modulation has been found to result in suppressed ECM degradation [59,60].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Moreover, MMP-2 has been shown to be upregulated in rat models of choline deficiency-mediated liver cirrhosis [54][55][56][57] and a similar pattern of expression has been observed for TIMP-1 (a) (b) Figure 1 Representative photos indicating the expression of the studied proteins (by brown staining) in the: (a) myocardium, interstitium and vessels; (b) interstitium and vessels (9200). [54,57,58], TIMP-2 [54] and MMP-9 [57]. On the contrary, the impact of inadequate levels of carnitine on MMPs modulation has been found to result in suppressed ECM degradation [59,60].…”
Section: Discussionmentioning
confidence: 55%
“…Unfortunately, most of these studies concerned mainly the liver since choline deficiency is a well‐established model of nonalcoholic fatty liver disease . Moreover, MMP‐2 has been shown to be upregulated in rat models of choline deficiency‐mediated liver cirrhosis and a similar pattern of expression has been observed for TIMP‐1 , TIMP‐2 and MMP‐9 . On the contrary, the impact of inadequate levels of carnitine on MMPs modulation has been found to result in suppressed ECM degradation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All blood examination including total cholesterol, triglycerides, HDL cholesterol, LDL cholesterol, fasting blood glucose (FBG), HbA1c, creatinine, and C‐reactive (CRP) was measured after an overnight fast of at least 12 h. Serum creatinine was measured by enzymatic method with commercial kits. HDL elution was separated using fast protein liquid chromatography and levels of TBARS in serum and HDL elution were detected with a commercial TBARS kit (Beyotime, China), which were quantified using malondialdehyde (MDA) as a standard .…”
Section: Methodsmentioning
confidence: 99%
“…The role of AR in the development of complications in diabetes is well-established (4). Additionally, hepatic AR expression has been observed to be induced in a number of liver disease conditions, including alcoholic liver disease, non-alcoholic fatty liver disease, hepatitis, cirrhosis and hepatocellular carcinoma (5)(6)(7)(8). It was previously reported that overexpression of AR induced the production of ROS and TNF-α in liver cells, and that administration of the AR inhibitor zopolrestat attenuated methionine-choline-deficient diet-induced hepatosteatosis and liver inflammation (8,9).…”
Section: Introductionmentioning
confidence: 99%